2022
DOI: 10.1038/s41467-022-32786-z
|View full text |Cite
|
Sign up to set email alerts
|

Genomic surveillance of SARS-CoV-2 Omicron variants on a university campus

Abstract: Novel variants continue to emerge in the SARS-CoV-2 pandemic. University testing programs may provide timely epidemiologic and genomic surveillance data to inform public health responses. We conducted testing from September 2021 to February 2022 in a university population under vaccination and indoor mask mandates. A total of 3,048 of 24,393 individuals tested positive for SARS-CoV-2 by RT-PCR; whole genome sequencing identified 209 Delta and 1,730 Omicron genomes of the 1,939 total sequenced. Compared to Delt… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
28
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(30 citation statements)
references
References 56 publications
2
28
0
Order By: Relevance
“…Summarizing, the case illustrates that an Omicron peak took place during a time when classes were not in session, and the return to class in 2022 was marked by rapidly falling disease incidences in the department, despite in-person classes, confirming evidence from the respective studies in U.S. universities [ 14 , 15 , 16 ]. Moreover, the department’s in-class instruction is not an appreciable source of COVID-19 transmission only under the setting of mandatory masking, which is in agreement with the relevant findings in the literature [ 14 ].…”
Section: Discussionsupporting
confidence: 61%
See 1 more Smart Citation
“…Summarizing, the case illustrates that an Omicron peak took place during a time when classes were not in session, and the return to class in 2022 was marked by rapidly falling disease incidences in the department, despite in-person classes, confirming evidence from the respective studies in U.S. universities [ 14 , 15 , 16 ]. Moreover, the department’s in-class instruction is not an appreciable source of COVID-19 transmission only under the setting of mandatory masking, which is in agreement with the relevant findings in the literature [ 14 ].…”
Section: Discussionsupporting
confidence: 61%
“…In the first category, efforts were made to assess the control plans used for reopening universities (e.g., Boston University in [ 4 ], Harvard/Boston/Duke/Northeastern in [ 5 ], Bristol (UK) in [ 6 ], Southern California in [ 7 ], Purdue in [ 8 ], Tulane in [ 9 ], Clemson in [ 10 ]); or to develop relevant susceptible–exposed–infected–recovered (SEIR) or agent-based (ABM) models in a university environment (e.g., Emory University in [ 11 ], University of Illinois in [ 12 ]). In the second category, research was focused on studying how COVID-19 containment protocols decreased transmission among university students (e.g., Saint Louis University in [ 13 ], Boston University in [ 14 ]) and to assess how the Omicron variant was established in universities (e.g., Harvard/Boston/Northeastern in [ 15 ], University of Washington in [ 16 ]).…”
Section: Background From the Literaturementioning
confidence: 99%
“…This suggests that Omicron is able to evade immunity induced in vaccinated individuals, providing a likely explanation for the rapid surge in Omicron in countries where a large proportion of individuals are fully vaccinated. Previous work has also quantified the reproductive number or relative growth advantage of Omicron in particular countries or settings, showing it to exceed that of previous emerging variants ( Pearson et al., 2021 ; Weil et al., 2022 ) and to be greater among vaccinated individuals ( Paton et al., 2022 ).…”
Section: Introductionmentioning
confidence: 99%
“…2). Twenty-two studies were from populations primarily of European ancestry [8,32,[40][41][42][43][44][45][46][47][48][49][50][51][52][53][54][55][56][57][58][59], eight studies on East Asians [60][61][62][63][64][65][66][67], three studies on South Asians [68][69][70], three studies on Latinos [71][72][73], four studies on populations in Africa [74][75][76][77], and one study from West Asia (Turkey [78]). The location of studies, with the prevalence indicated by the color intensity, and the cohort size indicated by the size of the circles, shows that Western countries report the highest prevalence, while studies from East Asia and Africa report the lowest prevalence (Fig.…”
Section: Properties Of Studiesmentioning
confidence: 99%
“…We did not attempt to resolve whether omicron sub-variants have different effects on olfactory dysfunctionthere are too few studies yet that report effects of subvariants on loss of smell [49,51,57]. Some cohorts of the studies were ethnically mixed, but the exact ethnic composition of the cohort was reported in only a few studies (e.g.…”
Section: Limitations Of Our Reviewmentioning
confidence: 99%